2006
DOI: 10.1111/j.1528-1167.2006.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased IH in Hippocampal Area CA1 Pyramidal Neurons after Perinatal Seizure‐inducing Hypoxia

Abstract: Summary:Purpose: The hyperpolarization-activated cation current (I H ) has been proposed to play a role in some forms of epileptogenesis, as it critically regulates synaptic integration and intrinsic excitability of principal limbic neurons and can be pathologically altered after experimentally induced seizures. In hippocampal CA1 pyramidal neurons, I H is functionally decreased after kainate-induced status epilepticus in adult rats but is increased after hyperthermia-induced seizures in immature rat pups. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Similarly, the spontaneously epileptic WAG/Rij rat exhibits reduced I h associated with increased R in and enhanced synaptic summation (Kole et al 2007;Strauss et al 2004). Perinatal seizures induced by hypoxia are also accompanied by a downregulation of I h (Zhang et al 2006). The present study indicates that reductions in I h associated with increases in cellular excitability and enhanced EPSP summation are found in a nonchemically induced malformation epilepsy model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the spontaneously epileptic WAG/Rij rat exhibits reduced I h associated with increased R in and enhanced synaptic summation (Kole et al 2007;Strauss et al 2004). Perinatal seizures induced by hypoxia are also accompanied by a downregulation of I h (Zhang et al 2006). The present study indicates that reductions in I h associated with increases in cellular excitability and enhanced EPSP summation are found in a nonchemically induced malformation epilepsy model.…”
Section: Discussionmentioning
confidence: 99%
“…contrary, acute hypoxia caused a disappearance of I h in inspiratory brainstem neurons and dorsal root ganglion neurons (Gao et al, 2006;Mironov et al, 2000). In addition, a partial inhibition of I h , without significant shift of voltage-dependent activation, was observed in hippocampal CA1 pyramidal neurons after neonatal hypoxia in vivo (Zhang et al, 2006a). Different from the above observations, this study revealed that I h in striatal cholinergic interneurons was significantly decreased early (3 h) after transient forebrain ischemia and suggested that the postischemic inhibition of I h might be caused by a negative shift of the voltage dependence of I h activation.…”
Section: Mechanisms Of Postischemic Decrease Of I H In Cholinergic Inmentioning
confidence: 91%
“…Thus, regulation of I h may cause profound changes in the membrane excitability of cholinergic interneurons. Several lines of evidence have shown that I h in neurons is very sensitive to ischemic insults (Erdemli and Crunelli, 1998;Gao et al, 2006;Mironov et al, 2000;Ray et al, 2003;Zhang et al, 2006a). However, the role of I h in ischemiainduced neuronal damage remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological alteration of I h has been shown in several models of seizure-inducing epileptogenesis or increased susceptibility to seizure (Shah et al, 2004;Zhang et al, 2006;Dugladze et al, 2007). Several studies suggest that downregulation of I h can be proepileptogenic (Peng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%